School visits to a physics research laboratory using virtual reality. (1st November 2022) - De Angelis, Ilaria; Budano, Antonio; De Pietro, Giacomo; Martini, Alberto; Postiglione, Adriana
Abstract: School visits to research laboratories or facilities represent a unique way to bring students closer to science and Science, Technology, Engineering and Mathematics careers. However, such visits can be very expensive for students and teachers, in terms of both time and money. In this paper, we present a possible alternative to on-site visits consisting in an activity addressed to high school students that makes use of a Virtual Reality application to make them 'enter' into a particle physics experiment. This proposal can represent a valid way of guaranteeing a visit to a research centre for all schools, regardless of their social or geographical origin. We describe the tests we carried out with a focus group of teachers and their students, and the obtained results.